Chapter 28 Genetics and cell biology of calcitonin action - Zaidi, M; Moonga, B; Pazianas, M; Shankar, V; Huang, C (1998)
Calcitonin is a 32-amino acid circulating hormone involved in skeletal homeostasis. Its primary target cell is the osteoclast, the bone-resorbing cell. Low picomolar concentrations of calcitonin inhibit bone resorption and produce a characteristic morphological change in isolated osteoclasts. The latter change has been separated biophysically into quiescence (Q) and retraction (R) components. Both components are involved in the inhibition of bone resorption, but are nevertheless distinct. The Q effect is mediated by a cholera toxin-sensitive Gs-like G protein involving a cyclic AMP-dependent pathway. The R effect is triggered by a rise of cytosolic [Ca2+] and probably involves the activation of a pertussis toxin-sensitive Gq-like G protein. The parallel activation pathways appear to be coupled proximally to separate calcitonin receptor subtypes. One of these cross-reacts with calcitonin and its related peptides, amylin and calcitonin gene-related peptide, while the other appears highly calcitonin-specific. However, in the renal epithelial cells, there is evidence for differential coupling of a single receptor to more than one transduction pathway. This occurs in a cell cycle-dependent manner. Two members of the calcitonin receptor family, the porcine renal receptor and the human ovarian receptor, have been cloned and sequenced. Both are of a high affinity (nM) and are functionally coupled to increases in intracellular cyclic AMP. The recombinant porcine renal calcitonin receptor also displays coupling to the phospholipase C-IP3 system. Both receptors show little (<12%) sequence similarity to other reported G protein-coupled receptors, except with the PTH/PTHrP and secretin receptors (>30%), indicating that the receptors for these hormones represent a new family of G protein-coupled receptors with unique structural and functional properties. © 1998 Elsevier B.V. All rights reserved.